Star Wars year by year a visual history. - Hidalgo, Pablo; Wallace, Daniel 1970-; Windham, Ryder (London Dorling Kindersley Limited, 2016)
The definitive history of "Star Wars" chronicling four decades of the world of "Star Wars"; decade by decade, year-by-year, month-by-month. Everything is covered, from the influences and creation of all six "Star Wars" movies, to the toys, books and video games that have shaped the "Star Wars" dynasty. The month-by-month format is brought to life by images from the movies, TV series, comic books and more.
Life before Star Wars Ryder Windham -- The original trilogy (1973-1983) Ryder Windham -- Between the trilogies (1984-1996) Daniel Wallace -- The prequel trilogy (1997-2005) Pablo Hidalgo -- Clone Wars & beyond (2006-2010) Pablo Hidalgo -- Star Wars: a new era (2013-2016) Pablo Hidalgo.
Prints in envelope attached to inside front cover.
Previous edition: 2012.
In slip case.
Includes index.
Keywords: Star Wars films -- Miscellanea; Star Wars films -- History and criticism; Star Wars films